The invisible web - Karst, Patrice; Lew-Vriethoff, Joanne (New York ; Boston : Little, Brown and Company, 2020)
Illustrations and easy-to-read text reveal that there are strings connecting people all over the world, that become tangled sometimes but always help us be one big family.
Keywords: Love -- Fiction; Belonging -- Fiction